(NfUNKCII KOMPLEKSNOGO PEREMENNOGO (B: (NoPERACIONNOE IS^ISLENIE (B: (NtEORIQ USTOJ^IWOSTI (B/ s - (NkRASNOW(B, (NmIHAIL lEONTXEWI^s; (NkISELEW(B, (NaLEKSANDR iWANOWI^s; (NmAKARENKO(B, (NgRIGORIJ iWANOWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1981)
(NsPISOK LIT(B. (NS(B. 303s
Keywords: (NoPERACIONNOE IS^ISLENIEs; (NfUNKCII KOMPLEKSNOGO PEREMENNOGOs; (NuSTOJ^IWOSTX(B, (NTEORIQs